ANGELA CARTER'S LIZZIE BORDEN: HERSTORY - Sardinha Caldeira, Carla Daniel [UNESP]; Rapucci, Cleide Antonia [UNESP] (Centro Univ Uniabeu, 2019)
This article aims to analyze the English author Angela Carter's short story, The Fall River Axe Murders found in her book of short stories Black Venus (1985). Such analysis takes into account the facts of Lizzie Borden's life that served as an inspiration to the short story which we see as a way for the author to promote herstory - that means telling Lizzie Borden's story through her perspective, considering the difficulties she had for being a woman in a Puritan society. Furthermore, we use texts such as Schofield's (1993), Lizzie Borden took an ax: history, feminism and American culture that provided us the real data about Lizzie's life; we also use feminist texts like the one by Harding (1985), Os Misterios da Mulher, for example. The goal is to show the subversive way which Carter revisits Lizzie Borden's story through her tale.
Keywords: Angela Carter; The Fall River Axe Murders; Lizzie Borden